Analysis of Antibiotic Resistance of Vibrio Сholerae Isolated From Environmental Objects in Russia in 2019 - N. A. Selyanskaya; L. A. Egiazaryan; M. I. Ezhova; N. I. Pasyukova; S. O. Vodopyanov (Антибиотики и Химиотерапия, 2021)
The aim of the study was to analyze the resistance to antibacterial drugs of Vibrio cholerae strains isolated from environmental water bodies on the territory of Russia in 2019.V.cholerae O1 El Tor (14) and V.cholerae nonO1/nonO139 strains were used in this work. Sensitivity/resistance to 11 antibacterial drugs was determined using the method of serial dilutions in a solid nutrient medium. The presence of drug resistance genes was determined using real-time PCR. Fluctuations in sensitivity/resistance of V.cholerae were found in various years. The phenotypic resistance of the strains to tetracycline and trimethoprim/sulfamethoxazole correlated with the presence of the tetR and dfrA1 genes in them. The presence of ICE was not detected in V.cholerae strains containing the tetR and qnrVC1 genes. The variability and wide spectrum of V.cholerae resistance require close attention to the problem of antibiotic resistance of cholera. The detection of ICE in the studied V.cholerae strains, as well as antibiotic resistance genes not associated with ICE elements, emphasize the need for molecular genetic monitoring of V.cholerae antibiotic resistance.